THE ROLE OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN IMPROVING COMMUNITY WELFARE ACCORDING TO ISLAMIC ECONOMIC PERSPECTIVE - yekti purwo asih (J-MD Jurnal Manajemen Dakwah, 2021)
The aim of this research is to debrief the research and analysis references (1) To find out what are the roles of Micro, Small and Medium Enterprises in improving the welfare of the community. (2) To find out what are the roles of Micro, Small and Medium Enterprises in improving the welfare of society according to the perspective of Islamic Economics. According to the research focus raised, the type of research that researchers use is qualitative research which will produce descriptive data in the form of written data and not numbers. Qualitative research methodology is a research method used to examine in natural object conditions (natural setting) is also known as an ethnographic method, because initially this method was mostly used for research in the field of cultural anthropology, referred to as qualitative research because the data collected and analysis are more qualitative in nature. Based on the results of the analysis after conducting research and discussion, the following conclusions were obtained: (1) Micro, Small and Medium Enterprises in Pontianak City are already good, it can be seen from the results of the study that 28 respondents have seen an increase in welfare by 70%. With this the tempe business has a very important role for the welfare of the community and increases the income of the surrounding community so that it can meet their daily needs such as food, as well as other needs such as housing, family health and the need for the education of their children. (2) Overview of Micro, Small and Medium Enterprises in improving the welfare of society according to the perspective of Islamic economics can be seen in terms of production, namely providing and creating something of value and useful to society in the form of goods and services. The goods in question are the results of their production, namely tempe, while services are production activities that have provided positive opportunities for the surrounding community in terms of employment. This tempe business has fulfilled the production process and fulfillment of income as stipulated in Islam so that it can improve the economic welfare of the people of Pontianak City, but only up to the fulfillment of Dharuriyat (primary) and Hajiyat (secondary) needs, while Tahsiniyat (tertiary) needs have not been fulfilled.